16 Beyond the Breeding Soundness Exam: The Evaluation of the Motility and Viability of Sperm Cells as Well as a Quantification and Evaluation of Mirna 26a-5p and Mirna 574, as Parameters of Bull Infertility. (8th March 2022) - Ruemke, Heather R; Runyan, Cheyenne L; Waddell, Jolena N; Roper, David; Daigneault, Brad; Poe, Brant
Abstract: Sperm cryopreservation is an important tool for assisted reproductive techniques, nonetheless there are major factors associated with reduced longevity and poor survivability of cryopreserved sperm in the female reproductive tract. Several studies have focused on molecular markers associated with apoptosis, mitochondrial integrity and oxidative stress in cryopreserved sperm. Research indicates miRNA 26a-5p and miRNA-574 exhibit anti-inflammatory attributes in some cells, by downregulating the effects on specific genes associated with inflammation and apoptosis. The aim of this study was to evaluate the quality of bovine semen, including a variety of breeds, post-thaw viability through kinetic screening using Computer Assisted Semen Evaluation (CASA). Cryopreserved semen samples from 5 bulls were thawed in a water bath (37.5°C for 35 s), then aliquoted in eppendorf tubes and initial CASA (Version 14 CEROS) measurements of total motility, progressive motility, and kinematic factors were assessed. Semen samples were placed in a heat block at 37.5 C for incubation for three 30-minute periods (30-minutes, 60-minutes, and 90-minutes) to measure thermoresistance and longevity to extrinsic factors influencing oxidative stress. After incubation periods 80 µL of each semen sample was screened on CASA. Data were analyzed using a Student-T in GraphPad Prism. Data are presented as LSMEANS and P-values ≤ 0.05 were considered significant and tendencies were considered at a P > 0.05. Semen samples were clustered into subpopulation threshold-based on sperm velocity and linearity at each time point. Levels of miRNA-574 and miRNA-26a-5p were quantified using qPCR. No significant differences of miRNA-574 or miRNA-26a-5p were detected in semen at post-thaw. Incubation of semen for 30-minutes resulted in total motility decrease (P = 0.02) and progressive motility tended to decline (P = 0.06). None of the semen was viable past the first 30-minute period. These data suggest that there are limited differences in thermoresistance in sperm in a rapid stress test. However, further research needs to be conducted to evaluate the cells on aspects of viability and overall function.